Generation of Monochromatic Radiation from a Multilayer Prismatic Target; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Shkitov D. A. Dmitriy Andreevich; Popov K. E.; Vukolov A. V. Artem Vladimirovich (Coherent Bremsstrahlung and Channelling Radiation, 2019)
Title screen